The ecosystem as helix: an exploratory theory‐building study of regional co‐opetitive entrepreneurial ecosystems as Quadruple/Quintuple Helix Innovation Models. (27th October 2017) - Carayannis, Elias G.; Grigoroudis, Evangelos; Campbell, David F. J.; Meissner, Dirk; Stamati, Dimitra
Abstract : Regions are increasingly being viewed as eco‐systemic agglomerations of organizational and institutional entities or stakeholders with socio‐technical, socio‐economic, and socio‐political conflicting as well as converging (co‐opetitive) goals, priorities, expectations, and behaviors that they pursue via entrepreneurial development, exploration, exploitation, and deployment actions, reactions and interactions. In this context, our paper aims to explore and profile the nature and dynamics of the Quadruple/Quintuple Helix Innovation System Model or Framework (government, university, industry, civil society, environment) as an enabler and enactor of regional co‐opetitive entrepreneurial ecosystems which we conceptualize as fractal, multi‐level, multi‐modal, multi‐nodal, and multi‐lateral configurations of dynamic tangible and intangible assets within the resource‐based view and the new theory of the growth of the firm. Co‐opetitive fractal innovation and entrepreneurship ecosystems are defined and discussed, and examples of regional innovation policies and programs are presented. Furthermore, the concept of multi‐level innovation systems is analyzed, taking into account the existence of knowledge clusters and innovation networks, while alternative aggregations of multi‐level innovation systems are proposed based on their spatial (geographical) and non‐spatial (research‐based) functional properties.